Mechanistic and Therapeutic Advances in Colon Cancer: A Systematic Review - Xuena Li; Ying Han; Aihua Zhang; Jianhua Miao1; Hui Sun; Guangli Yan; Fangfang Wu; Xijun Wang (Open Journal of Proteomics and Genomics - Peertechz Publications, 2019)
Colon cancer is a common gastrointestinal malignancy in daily life and is the third most common cancer. So far, the global incidence of colon cancer has risen every year. Colon cancer mortality accounts for half of the incidence, colon cancer mortality ranks fifth in malignant tumor mortality, which seriously threatens human survival and health. This article refers to the latest domestic and foreign related articles related to colon cancer. It summarizes common and emerging screening methods for colon cancer which can make early detection and early treatment of the disease for reducing the deterioration and metastasis of colon cancer. It discusses the diagnostic markers of colon cancer found out in recent years and its mechanism of action, to improve the level, accuracy and scientificity of diagnosis. This article points out that the metastasis of colon cancer is the main cause of death in patients with colon cancer and to discuss the mechanism of its metastasis. It also summarizes the therapy thereof and advantages and disadvantages of colon cancer from different aspects such as intestinal flora, targeted therapy, traditional Chinese medicine and western medicine. Finally, the article summaries some methods that can effectively prevent colon cancer, reduce the occurrence of colon cancer from the source and improve people's quality of life.